Household solid waste disposal pattern in Malaysia - Md Jusoh, Zuroni; Osman, Syuhaily; Muhammad Ariff, Afida Mastura; Mat Salleh, Roslina (Faculty of Human Ecology, Universiti Putra Malaysia, 2020)
The progress of a developing country has resulted in a growing increase in solid waste. The growing population and the urbanization process have raised the problem of excessive use in today's society where it has adversely affected environmental sustainability. Zero waste management is an activity that maximizes the practice of recycling and minimizes excess waste, reduces usage and ensures that goods used can be recycled, reused, repaired and composted. The main objective of this study is to examine the pattern of household solid waste disposal among Malaysian consumers. A total of 605 respondents were involved in this study via multistage random sampling. The study area was divided into four main zones in Peninsular Malaysia, namely the north, west, south and east zones. One state among the gazetted states was selected from each of the zone and the main city was chosen as the location of the study resulting in four states namely Penang, Putrajaya Federal Territory, Negeri Sembilan and Pahang. The relevant cities were Seberang Perai, Putrajaya, Seremban and Kuantan. Visitors coming to the main mall in each city were approached to participate in the survey. The data were collected through a set of self-administered questionnaires and analysed using SPSS version 24 software. Respondents in this study involved various levels of age, race, gender, education level and income. Results found that most respondents (65.8%) knew about the zero waste program and more than half of the respondents (53.2%) were segregating solid waste at home. In addition, respondents also segregate solid waste almost daily according to the predetermined categories. It can be concluded that although respondents know about segregating of solid waste and always segregating but respondents still do not know about the collection system done by the authorities and ultimately it implicates the government and stakeholders to be able to play their role in the management of solid waste in the direction of these zero wastes.